Solvent minimization induces preferential orientation and crystal clustering in serial micro-crystallography on micro-meshes, in situ plates and on a movable crystal conveyor belt - Soares, Alexei S (Journal of synchrotron radiation, 2014)
X-ray diffraction data were obtained at the National Synchrotron Light Source from insulin and lysozyme crystals that were densely deposited on three types of surfaces suitable for serial micro-crystallography: MiTeGen MicroMeshes™, Greiner Bio-One Ltd in situ micro-plates, and a moving kapton crystal conveyor belt that is used to deliver crystals directly into the X-ray beam. 6° wedges of data were taken from ∼100 crystals mounted on each material, and these individual data sets were merged to form nine complete data sets (six from insulin crystals and three from lysozyme crystals). Insulin crystals have a parallelepiped habit with an extended flat face that preferentially aligned with the mounting surfaces, impacting the data collection strategy and the design of the serial crystallography apparatus. Lysozyme crystals had a cuboidal habit and showed no preferential orientation. Preferential orientation occluded regions of reciprocal space when the X-ray beam was incident normal to the data-collection medium surface, requiring a second pass of data collection with the apparatus inclined away from the orthogonal. In addition, crystals measuring less than 20 µm were observed to clump together into clusters of crystals. Clustering required that the X-ray beam be adjusted to match the crystal size to prevent overlapping diffraction patterns. No additional problems were encountered with the serial crystallography strategy of combining small randomly oriented wedges of data from a large number of specimens. High-quality data able to support a realistic molecular replacement solution were readily obtained from both crystal types using all three serial crystallography strategies